Proceedings of the ACM Recommender Systems Challenge 2018 2018
DOI: 10.1145/3267471.3267476
|View full text |Cite
|
Sign up to set email alerts
|

Using Adversarial Autoencoders for Multi-Modal Automatic Playlist Continuation

Abstract: The task of automatic playlist continuation is generating a list of recommended tracks that can be added to an existing playlist. By suggesting appropriate tracks, i. e., songs to add to a playlist, a recommender system can increase the user engagement by making playlist creation easier, as well as extending listening beyond the end of current playlist. The ACM Recommender Systems Challenge 2018 focuses on such task. Spotify released a dataset of playlists, which includes a large number of playlists and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Thus, the models can also be applied to similar tasks in other domains, which could also benefit of the use of metadata. For example, we have previously shown that metadata are beneficial for automatic playlist continuation [12].…”
Section: Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the models can also be applied to similar tasks in other domains, which could also benefit of the use of metadata. For example, we have previously shown that metadata are beneficial for automatic playlist continuation [12].…”
Section: Threats To Validitymentioning
confidence: 99%
“…For the latter, the task is for professional indexers to choose representative annotations from a domain-specific thesaurus in order to label scientific papers. The existing body of works is typically concerned with one-off recommendation, e. g., recommendations of scientific collaborators [8], suggestion of which paper or news to read next [1,9,10], or recommending an open sequence of items, e. g., music recommendations on Spotify, which are continuously extended as long as the users are listening [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…VAE-AR [66] 2017 ✓ ✓ ✓ RGD-TR [71] 2018 ✓ ✓ ✓ aae-RS [136] 2018 ✓ ✓ ✓ SDNet [26] 2019 ✓ ✓ ✓ ATR [89] 2019 ✓ ✓ ✓ AugCF [127] 2019 ✓ ✓ ✓ RSGAN [138] 2019 ✓ ✓ ✓ RRGAN [24] 2019 ✓ ✓ ✓ UGAN [129] 2019 ✓ ✓ ✓ LARA [107] 2020 ✓ ✓ ✓ CGAN [28] 2020 ✓ ✓ ✓ Context-aware Rec. Temporal-aware RecGAN [8] 2018 ✓ ✓ ✓ NMRN-GAN [126] 2018 ✓ ✓ ✓ AAE [116] 2018 ✓ ✓ ✓ PLASTIC [147] 2018 [25] 2019 ✓ ✓ ✓ Geographical-aware Geo-ALM [75] 2019 ✓ ✓ ✓ APOIR [148] 2019 ✓ ✓ ✓ Cross-domain Rec. VAE-GAN-CC [82] 2018 ✓ ✓ ✓ RecSys-DAN [121] 2019 ✓ ✓ ✓ FR-DiscoGAN [59] 2019 ✓ ✓ ✓ DASO [39] 2019 ✓ ✓ ✓ CnGAN [88] 2019 ✓ ✓ ✓ Fashion Rec.…”
Section: Model Namementioning
confidence: 99%
“…Temporal-aware RecGAN [8] 2018 ✓ ✓ ✓ NMRN-GAN [126] 2018 ✓ ✓ ✓ AAE [116] 2018 ✓ ✓ ✓ PLASTIC [147] 2018 [25] 2019 ✓ ✓ ✓ Geographical-aware Geo-ALM [75] 2019 ✓ ✓ ✓ APOIR [148] 2019 ✓ ✓ ✓ Cross-domain Rec. VAE-GAN-CC [82] 2018 ✓ ✓ ✓ RecSys-DAN [121] 2019 ✓ ✓ ✓ FR-DiscoGAN [59] 2019 ✓ ✓ ✓ DASO [39] 2019 ✓ ✓ ✓ CnGAN [88] 2019 ✓ ✓ ✓ Fashion Rec.…”
Section: Collaborative Recommendationmentioning
confidence: 99%
“…Clearly there are very significant differences in the two approaches, even though both utilize autoencoders. To delve deeper into these differences and how they might have resulted in such a large difference in scores, we recommend reading both [48] and [53].…”
Section: Other Notable Approachesmentioning
confidence: 99%